Complications Associated with Transradial Access in Coronary Angiography and Intervention - Khalid, Fahad; Khan, Bakht Umar; Arif, Nayyar (Indus Journal of Bioscience Research, 2024)
Objectives: The study’s goal is to compare distal and traditional methods in order to investigate the complications related to transradial access in coronary angiography and intervention. Materials and Methods: This study was conducted at the Department of Cardiology, AFIC, Rawalpindi, Pakistan in the period from January 2022 to December 2023 in patients with the age of 18 years and more who underwent coronary angiography or percutaneous coronary intervention via radial artery. Inclusion required the participant to sign an informed consent form and for data capture a complete record review. Results: The study conducted among 300 patients showed that the complication rate of the procedure was 10%. In particular, there was a significant and highly statistically significant difference to complications where distal transradial intervention had a rate of 5% and conventional approach had 15%. The most frequent complication documented was radial artery spasm which was managed using appropriate medications. Conclusion: Transradial access for coronary procedures are safe particularly with the distal located access which can potentially add more value to the improvement of the patient. These studies underscore the importance of technical improvement involving general and procedural aspects of care to prevent complications during cardiology procedures.